Asymmetric Covalent Triazine Framework for Enhanced Visible‐Light Photoredox Catalysis via Energy Transfer Cascade. Issue 27 (4th June 2018) - Huang, Wei; Byun, Jeehye; Rörich, Irina; Ramanan, Charusheela; Blom, Paul W. M.; Lu, Hao; Wang, Di; Caire da Silva, Lucas; Li, Run; Wang, Lei; Landfester, Katharina; Zhang, Kai A. I.
Abstract: Complex multiple‐component semiconductor photocatalysts can be constructed that display enhanced catalytic efficiency via multiple charge and energy transfer, mimicking photosystems in nature. In contrast, the efficiency of single‐component semiconductor photocatalysts is usually limited due to the fast recombination of the photogenerated excitons. Here, we report the design of an asymmetric covalent triazine framework as an efficient organic single‐component semiconductor photocatalyst. Four different molecular donor–acceptor domains are obtained within the network, leading to enhanced photogenerated charge separation via an intramolecular energy transfer cascade. The photocatalytic efficiency of the asymmetric covalent triazine framework is superior to that of its symmetric counterparts; this was demonstrated by the visible‐light‐driven formation of benzophosphole oxides from diphenylphosphine oxide and diphenylacetylene. Abstract : The molecular design of an asymmetric covalent triazine framework as an efficient single‐component semiconductor photocatalyst is presented. Enhanced photocatalytic efficiency is achieved by means of a light‐induced multiple intramolecular energy transfer cascade.